MANAJEMEN HUMAS DALAM MENINGKATKAN PARTISIPASI MASYARAKAT TERHADAP PENGEMBANGAN MADRASAH DI MTs DARUSSALAM ARIYOJEDING REJOTANGAN - Fakhruddin Al Farisy (STAI KH. Muhammad Ali Shodiq, 2023)
Public Relations Management (PR) is a one of the influential component of education, especially in the educational management process which will later determine the success of the educational institution. Public relations is a two-way communication bridge between the school and the community, both of which complement each other and must synergize with each other in order to create feedback for the educational institution. Community participation is the main support in providing education. This is stated in the National Education System Law No. 20 of 2003, namely the importance of community participation, so educational institutions must manage it in a professional managerial manner. This research into analyze public relations management in increasing community participation in madrasa development implemented at MTs Darussalam Ariyojeding Rejotangan Tulungagung. The focus of this research is how public relations management can increase community participation in madrasa development. This research uses a qualitative approach with a multisite study design. Data collection was carried out using in-depth interview techniques, observation and documentation. Data analysis techniques include data reduction, data presentation and drawing conclusions. Checking the validity of the findings was carried out with researcher participation and triangulation. Research information from the institution's stage holders, especially public relations administrators. The research results obtained are: 1) the steps for planning a public relations work program consist of; (a) Analysis of comprehensive needs; (b) Analysis of situations and conditions; (c) Evaluation through joint deliberation. 2) Implementation of public relations management activity programs through several media; (a) Print media; (b) Visual media; (c) Audiovisual media; 3) Evaluation of the public relations management activity program is divided into 2 parts: small and large scale evaluation. Keywords: Management PR, Increasing Community Participation